Management of Breast Cancer with Curcumae Rhizoma: A Therapeutic Approach - Atik Diah Mutiara Ningsih; Rafif Shidqi; Syarinta Adenina (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Breast cancer has the highest incidence in women, covering 2.3 million new cases per year and a mortality rate of 23%. Therapeutic strategies applied in breast cancer treatment include surgery, chemotherapy, endocrine therapy, and radiation. All of these therapies have relatively high side effects, so alternative therapies are needed that are more effective with minimal side effects. One of the herbs known to be effective in treating breast cancer is Curcumae Rhizoma from Curcumae longa extract. The essential components of this drug are Curcumol and Curcumin. Literature searches were obtained from various online portals such as Pubmed, Google Scholar and Science Direct using the keywords